Ability to self-care agency and health quality of life of patients attending the outpatient department of geriatrics at Guillermo Almenara Irigoyen National Hospital, Lima, 2015 - Olazo Obando, Fressia Angélica (2019)
Objetive: The objective of the present study is to determine the relation between the capacity of self-care agencyand life quality for the health of the elderly in the Outpatient Geriatric Service at the Guillermo Almenara IrigoyenHospital. Methods: The study was descriptive, cross -sectional, with a correlation design in which 175 peopleparticipated, ages 60 to 85; data was obtained through the ASA Scale and the SF- 12 v2 Questionnaire. Results:The results indicate that there is a direct and significant relation between the capacity of self-care agency and thequality of life in health, (rho=0.284, p=0.000), as well as in the capacity of self-care agency and the dimensionsof vitality (rho=0.430, p=0.000), general health (rho=0.249, p=0.001), physical function (rho=0.364, p=0.000)and mental health (rho=0.250, p=0.001); significant relation was not found between the agency capacity of selfcare and the dimensions of physical role (rho=0.084, p=0.268) emotional role (rho=0.101, p=0.185), body pain(rho=0.092, p=0.225) and social functioning (rho=0.129, p=0.088). It is concluded that the capacity of self-careagency and the quality of life in health are related variables.